PSYCHOLOGICAL FEATURES OF EMOTIONAL INTELLIGENCE DEVELOPMENT IN FUTURE TEACHERS (International journal of artificial intelligence, 2025)
This article explores the psychological features of emotional intelligence development in future teachers. Emotional intelligence (EI) is a vital factor in the professional formation of teachers, influencing their communication, empathy, self-regulation, and decision-making skills. The paper analyzes the psychological mechanisms that contribute to the development of emotional intelligence among pedagogical students and emphasizes its importance in effective teaching and classroom management.